Germinal, pour un théâtre sans drame ni roman - Frantz, Pierre (Status Quaestionis, 2022)
The analysis of the adaptation of Zola’s Germinal by Jean-Pierre Vincent at the time of his arrival in Strasbourg (1975) gives the chance to develop several aspects relevant to the relationship between novel and theatre. From a formal point of view, we are going to see how aesthetics, asserted by Vincent and implemented by his staff, tends to take precedence over narration and dialogue and how, in the novel, aesthetics favours something that may seem foreign to theatre, descriptions. We will see how Vincent takes hold, so to speak, of the Brechtian theories on epic theatre, only to rework them from a new perspective; how his work aims at questioning the relationship between intellectuals and working class; how he challenges the ideas of representation and drama; finally, how he posits the idea of theatre work as teamwork.